Uncover valuable information and solutions with IDNLearn.com's extensive Q&A platform. Find the answers you need quickly and accurately with help from our knowledgeable and experienced experts.
Sagot :
Answer:
the 34 yrs Is wrong it will be 4yrs only.
Step-by-step explanation:
Let my present age=x years
After 12 years my age=x+12 years
4 years ago my age =x−4 years
According to the question,
x+12=3(x−4)
⇒x+12=3x−12
⇒3x−x=12+12
⇒2x=24
or x= 24/2 =12 years.
∴ my present age is 12 years.
hope this helps you.
Let the present age of let’s say todd be X
Todd’s age (x+12) will be 3 times as old as he was 4 years ago [3(x-4)]
i.e
x+12=3(x-4)
x+12=3x-12
2x=24
X=12.
Hence Todd’s present age is 12.
Todd’s age (x+12) will be 3 times as old as he was 4 years ago [3(x-4)]
i.e
x+12=3(x-4)
x+12=3x-12
2x=24
X=12.
Hence Todd’s present age is 12.
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. IDNLearn.com is your go-to source for accurate answers. Thanks for stopping by, and come back for more helpful information.